Study of the role of oxidative stress and antioxidants in SARS-CoV-2 infection: a systematic review (Research, Society and Development, 2022)
With the arrival of SARS-CoV-2, the world found itself in a war against the virus-caused disease. This can compromise systems such as the cell cycle, stress, immunological, and metabolic systems, leading to impairment of renin-angiotensin, which is involved in the functioning of vital organs. At the same time, there is an imbalance in the redox system, which is triggered by the disease's typical storm of inflammatory cytokines. These imbalances, along with the presence of previous diseases and advanced age, contribute to a poor prognosis of the disease. For these reasons, much has been speculated about the use of antioxidants to prevent or eliminate the virus. In this context, the purpose of this systematic review was to better understand the effects of antioxidants on SARS-CoV-2 infection. Using the Medline/Pubmed database, data from clinical and observational retrospective and prospective studies were explored, selecting a total of 25 studies. The sample size ranged from 12 to 4314 individuals and the average age was 55.27 ± 11.82. The majority of studies used vitamin D (n=10) as an intervention, followed by vitamin C (n=6), zinc (n=5), and phenolic compounds (n=4). Regarding the evaluation of the quality of the studies, an average score of 7.38 points for clinical studies and 9.28 points for observational studies was found, indicating good methodological quality. Despite some evidence pointing to the benefits of antioxidants against the disease, there is still no agreement on its true role, owing to a lack of robust evidence and discrepancy between published results.